Development and grain yield of barley genotypes according to sowing date - Mateus Possebon Bortoluzzi; Lucas Ughini Marques; Adriana Favaretto; Laura Valentina Caus Maldaner; Alessandra Gallina (Revista Thema)
This study aimed to determine the length of subperiods, development cycle, yield, and grain quality of barley genotypes at different sowing dates. Three experimental lines from a barley breeding program Barley01, Barley02, and Barley03 as well as three commercial cultivars ABI Invicta, ABI Valente, and ABI Rubi were sown in 2001 in the municipality of Passo Fundo. Also, lines Barley04, Barley05, and Barley06, in addition to ABI Invicta and ABI Valente, were sown in 2022 in the municipality of Coxilha. Sowings were carried out on June 1st, June 16th, and July 7th, 2021, in Passo Fundo and May 24th, June 15th, and July 4th, 2022, in Coxilha. The barley development cycle decreased from sowings carried out at the end of May until the beginning of July. Lines Barley02 and Barley06 showed higher precocity. A higher proportion of first-class grains was observed in early sowings in both locations. Barley grain yield depends on the genotype, location, and sowing date.